Investigating financial efficiency in steel industry companies: evidence from three-dimensional DEA approach - Kasra Ghafori (تصمیم گیری و تحقیق در عملیات)
Purpose: In general, efficiency is a criterion for evaluating the performance of a decision unit from different dimensions. Data envelopment analysis is a mathematical programming method for evaluating the performance of decision-making units. The purpose of this study is to measure the financial efficiency of firms by considering both incoming assets and financing.Methodology: In this research, a new method called the three-dimensional model of data envelopment analysis was introduced, and performance analysis was done on 10 active firms in Iran's steel industry for 5 years, from 2016 to 2021.Findings: The results showed that several firms have good performance in managing incoming assets but are inefficient in terms of financing. At the same time, some firms have poor management performance compared to inputs, but they are efficient in terms of financing. Therefore, when analyzing a firm's performance, an indicator that considers both inputs and financing at the same time is needed. According to this, we proposed a new measurement method and analyzed the current financial situation of each decision-making unit through the method of return to scale, and a path has been determined for financial improvement.Originality/Value: Attention to the effect of negative and destructive factors such as borrowings and debts of the decision-making unit in data envelopment analysis has been the key and different aspect of this study, compared to other previous studies. According to the literature review, using the redesigned DEA model has not been considered by Iranian researchers, and due to a new approach to data envelopment analysis, our approach has distinguished itself from the previous works.